14C levels in the vicinity of the Fukushima Dai-ichi Nuclear Power Plant prior to the 2011 accident. (June 2016) - Xu, Sheng; Cook, Gordon T.; Cresswell, Alan J.; Dunbar, Elaine; Freeman, Stewart P.H.T.; Hastie, Helen; Hou, Xiaolin; Jacobsson, Piotr; Naysmith, Philip; Sanderson, David C.W.; Tripney, Brian G.; Yamaguchi, Katsuhiko
Abstract: A 50-year-old Japanese cedar ( Cryptomeria japonica ) from Okuma, ∼1 km southwest of the Fukushima Dai-ichi Nuclear Power Plant, was cored and each annual ring was analysed for 14 C. The 14 C specific activity values varied from 330.4 Bq kg −1  C in the tree ring formed in 1971 to 231.2 Bq kg −1  C in the 2014 ring. During the periods 1971–1976 and 2011–2014, the 14 C specific activities are indistinguishable from the ambient background values. However, compared with the ambient atmospheric levels, the 14 C specific activities between 1977 and 2010 are significantly elevated, clearly indicating 14 C discharges from the reactors during their normal operations. In addition, the specific activities are positively correlated with the annual electricity generation values. The excess 14 C specific activities were <36 Bq kg −1  C, corresponding to an additional annual effective dose of <2 μSv via the food ingestion pathway in the study location. The primary wind direction is east-southeast/southeast with a frequency of ∼30%, in comparison to ∼20% frequency for the direction of the site under study (north-northeast/northeast). This would tend to indicate a similar magnitude of additional effective dose and consequently no significant radiological impact of atmospheric 14 C discharges from the FDNPP during the entire period of normal operations. Additionally, no 14 C pulse in activity can be observed in the year 2011 ring. This might be caused by a limited 14 C release from the damaged reactors during the accident or that the prevailing wind during the short period of release (11th–25th March 2011) was not in the direction of Okuma. Graphical abstract: Highlights: The 14 C variation in 1971–1976 and 2011–2014 is ascribed as an exponential decline. The 14 C discharge from FDNPP normal operation caused 14 C enrichment in 1977–2010. Total 53 TBq 14 C were released during the whole period of the normal operations. No visible accident 14 C pulse was observed in the year 2011 ring in Okuma. Additional dose from discharged 14 C to the public is negligible.